Doing harm: living organ donors, clinical research and The Tenth Man. Issue 2 (April 1995) - Elliott, C
Abstract : This paper examines the ethical difficulties of organ donation from living donors and the problem of causing harm to patients or research subjects at their request. Graham Greene explored morally similar questions in his novella, The Tenth Man.